Dynamics of coronary artery velocity flow during exercise echocardiography - Zagatina, Angela; Zhuravskaya, Nadezhda; Caprnda, Martin; Rodrigo, Luis; Kruzliak, Peter (Acta cardiologica, 2022)
PURPOSE: The aim of our study was to acquire non-invasive data from coronary flow velocity profiles during exercise in groups of healthy subjects and of patients with arterial hypertension. MATERIAL AND METHODS: We enrolled 83 patients into two groups: (1) 35 non-selected consecutive healthy subjects; (2) 25 consecutive patients with arterial hypertension. All the patients performed supine bicycle symptoms-limited tests. Throughout exercise the diastolic peaks of coronary flow velocity in LAD were recorded. Coronary flow velocity reserve (CFVR) was calculated off-line. Profiles of coronary artery velocity were acquired for all groups. The coronary artery flow parameters investigated were comparable in healthy and hypertensive patients at every stage. RESULTS: The average diastolic velocities were 54.8 ± 12.9 vs. 51.8 ± 12.2 cm/s, at 50 W; 69.2 ± 17.1 vs 64.4 ± 19.1 cm/s at 75 W; 70.7 ± 16.4 vs. 76.1 ± 19.0 cm/s at 100 W; 80.0 ± 16.0 vs. 72.9 ± 16.1 cm/s at 125 W; 83.7 ± 12.2 vs. 81.4 ± 17.0 at 150 W, p- non-significant, respectively. On average, the healthy group reached CFVR > 2.0 at a heart rate of 110-120 beats/min at 75 W. During supine bicycle exercise, healthy subjects and patients with arterial hypertension have a similar coronary artery flow velocity profile. CONCLUSION: The routine exercise echocardiography test can feasibly be supplemented with the additional measurement of coronary flow velocity during routine supine exercise stress tests, as the normal range of CFVR is reached before submaximal heart rate.
Keywords: Hypertension; Blood Flow Velocity; echokardiografie; hypertenze; lidé; Coronary Vessels; Humans; koronární cirkulace; koronární cévy; Coronary Circulation; rychlost toku krve; Echocardiography